THE CORRELATION OF MOTHER'S ROLE WITH THE ABILITY OF TOILET TRAINING IN CHILDREN - Tri Ratna Ningsih; Devian Rezky Ida Precilia (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Children's ability in doing toilet training was influenced by children's physical, psychological and emotional readiness, there had to be a positive role from parents especially mothers in the toilet training process. Problem that often encountered was many mothers who did not teach toilet training and letting children urinating or defecating in not appropriate place. The purpose of this study was to study the correlation of mother’s role with the ability of toilet training in children in PAUD and Miftahul Qulub Gondang Kindergarten. The study design was correlational analytic with cross-sectional approach. The population in this study were all mothers of PAUD students and Miftahul Qulub Gondang Kindergarten as many as 92 respondents. The sample was taken by the total sampling technique as many as 92 respondents. Data were collected using the questionnaire of mother’s role and questionnaire of children’s toilet training ability which had been tested for validity with 10 respondents, then collected with a statistical distribution (crosstab) presented in table form. The results showed that most mothers were able to do toilet training (82.4%). Mother with positive role could make children doing their toilet training. There was correlation of mother’s role with the ability of children’s toilet training in PAUD and Miftahul Qulub Kindergarten, Gondang. If mother's role was positive then children would succeed in conducting toilet training because the mother's role was one of the factors that strongly supported children’s ability in toilet training. Besides, mother with good teaching method would make successful toilet training process in children.